2013
DOI: 10.1155/2013/610235
|View full text |Cite
|
Sign up to set email alerts
|

Fault Diagnosis of Plunger Pump in Truck Crane Based on Relevance Vector Machine with Particle Swarm Optimization Algorithm

Abstract: Abstract. Promptly and accurately dealing with the equipment breakdown is very important in terms of enhancing reliability and decreasing downtime. A novel fault diagnosis method PSO-RVM based on relevance vector machines (RVM) with particle swarm optimization (PSO) algorithm for plunger pump in truck crane is proposed. The particle swarm optimization algorithm is utilized to determine the kernel width parameter of the kernel function in RVM, and the five two-class RVMs with binary tree architecture are traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Due to the topic of the paper, it is particularly important to refer to works in which the vibrations generated by a working machine are the input signal being the basis for the diagnosis. In the work [6] the authors monitored the behavior of a plunger pump in a truck crane through the acquisition of its vibrations in three dimensions. The spectra of the machine operations in a correct state were known, along with its operations spectra in five incorrect diagnostic states.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the topic of the paper, it is particularly important to refer to works in which the vibrations generated by a working machine are the input signal being the basis for the diagnosis. In the work [6] the authors monitored the behavior of a plunger pump in a truck crane through the acquisition of its vibrations in three dimensions. The spectra of the machine operations in a correct state were known, along with its operations spectra in five incorrect diagnostic states.…”
Section: Related Workmentioning
confidence: 99%
“…The drives are connected by rollers with toothed gears which reduce the rotary speed of the roller in the main lifting mechanism. In addition, the figure presents the location of vibration sensors which are placed on the rollers (1,6), pinion bearings (2,5) and on the supporting beam. Sensors 3 and 4 are, in fact, auxiliary ones and their task is to monitor the vibration level of the background.…”
Section: Object and Goal Of Monitoringmentioning
confidence: 99%
“…Lu et al [12] created an EEMD paving and optimized support vector regression method to detect faults and estimate the fault sizes of a piston pump based upon discharge pressure signals. On the other hand, vibration signal also reflects the performance of the piston pumps and the faults of piston pumps are generally accompanied by changes in vibration signal [14][15][16][17][18]. Jiang et al [14] found the fault vibration signals of hydraulic pump were often modulated by the impact and the fault features were concealed when it became fault.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of artificial intelligence, intelligent fault diagnosis techniques have also been developed, such as artificial neural networks (Gaing, 2004; Wu et al., 2007), support vector machine (Chunling et al., 2009; Kim and Lee, 2009), and linear discriminant analysis (Sakai et al., 2008). The application of these diagnosis techniques has been published in many works, including bearings (Yang and Tavner 2009; El-Thalji and Jantunen, 2015; Zhang et al., 2015), pumps (Du et al., 2013; Ding et al., 2015), engines (Macián et al., 2003), etc. However, most of the researches have put forward the fault diagnosis of the gear system, but most of them have the fault form of a single part – the multi-part coupling fault has not been put forward.…”
Section: Introductionmentioning
confidence: 99%